1980
DOI: 10.2527/jas1980.51189x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lactose on Gain, Feed Conversion, Blood, Bone and Intestinal Parameters in Postweaning Rats and Swine

Abstract: SummaryTwo trials were conducted to determine the effect of lactose on performance, bone integrity and certain blood constituents in postweaning rats and swine. The effect of lactose on calcium and phosphorus and percentage ash content of the small intestine was also determined. In both trials, average daily gains were not influenced by the feeding of diets containing 30% lactose. Feed conversion was depressed in both rats and pigs when 30% lactose was fed. Transitory diarrhea was observed in rats fed 30% lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
1
3
1
1
Order By: Relevance
“…Hens fed 1 and 2% lactose consumed less feed (105 and 106 g, respectively) than those fed 0 and 3% lactose (109 and 100 g, respectively). This does not agree with the findings of Moser et al (1980). They reported that lactose stimulated feed intake in swine.…”
Section: Resultscontrasting
confidence: 72%
“…Hens fed 1 and 2% lactose consumed less feed (105 and 106 g, respectively) than those fed 0 and 3% lactose (109 and 100 g, respectively). This does not agree with the findings of Moser et al (1980). They reported that lactose stimulated feed intake in swine.…”
Section: Resultscontrasting
confidence: 72%
“…There was no apparent difference in weight gain or feed efficiency between semisynthetic high and low Lac milk groups, which sup ported the findings of Massey and Davidson [7] and Moser et al [ 16]. The rat only absorbs 47% of the Lac present in the small intestine when Lac is supplemented at 30% [17].…”
Section: Diet Adaptationsupporting
confidence: 74%
“…Although Shortt et al [54] reported that lactose alone did not seem to alter bone mass or bone breaking strength in rats, and they demonstrated that lactose protected against the high salt intake-induced bone loss in weaning rats by enhancing calcium absorption. Moreover, in two trials using post-weaning rats and swine conducted by Moser et al [55], bone breaking strength was not altered by dietary lactose. However, in the post-weaning rat model, higher levels of lactose in the diet corresponded to increased skeletal calcium content.…”
Section: The Effect Of Lactose On Calcium Metabolism and Bone Healmentioning
confidence: 99%